2015
DOI: 10.1016/j.jor.2015.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single event vs multiple event soft tissue surgeries in the lower extremities with cerebral palsy

Abstract: When compared to groups, there was no significant difference. This study showed that both surgical techniques resulted in improvements in GMFCS and WeeFIM levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
6
0
3
Order By: Relevance
“…In ambulatory patients (GMFCS levels I, II and III), SEMS is widely accepted as the gold standard for improving gait. [9,22] It has been reported that surgical treatment is planned more accurately and the results are more successful by performing static and dynamic examination together. [4,14] A number of other studies in the orthopedic literature have also accepted a significant positive change in the level of GMFCS after SEMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ambulatory patients (GMFCS levels I, II and III), SEMS is widely accepted as the gold standard for improving gait. [9,22] It has been reported that surgical treatment is planned more accurately and the results are more successful by performing static and dynamic examination together. [4,14] A number of other studies in the orthopedic literature have also accepted a significant positive change in the level of GMFCS after SEMS.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] However, some authors suggest multiple surgical events (MSE), emphasizing the risks of simultaneous surgical procedures in dysfunctional muscle groups. [8,9] Besides, evaluation examinations related with the satisfaction of parents are not common in studies comparing the two methods. [10] There is also limited data comparing the clinical parameters after SEMS and MSE styles of treatment.…”
mentioning
confidence: 99%
“…8 Surgical procedures for lower extremity soft tissue such as tenotomy, tendon transfers, fractional or Z lengthening of the tendon can be performed to correct contractures and deformities of the joint to lengthen the spastic muscle. 9 SEMLS which has replaced the previous concept of single level surgery, has shown improved long term gait outcomes in both prospective and retrospective studies in bilateral CP. 10 Owing to poor financial statuses of many of the children in the study group and inadequate resources in the rehabilitation unit, surgery could not be performed at all three levels in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Bu nedenle SMILE (Sequential Multilevel Interventions in the Lower Extremities) denilen, alt ekstremitenin ardışık, çok seviyeli girişimlerle tedavisi önerilmiştir. [9,10] GMFCS 4-5 kuadriplejik hastalarda ortopedik cerrahi hasta bakımı (hijyeni), bacaklarını açabilmesi ve kolay giydirilebilmesi amacıyla uygulanır.…”
Section: Spasti̇si̇tede Ortopedi̇k Tedavi̇de Amaç Ve Zamanlamaunclassified
“…Her hastaya özel tedavi seçimi ve bir iki seansta çok seviyeli cerrahi girişim uygulaması yapılmalıdır. [2,9] Tendon-kas uzatma ameliyatları ile eklem hareket açıklığının arttırılması ana ilkedir. Tendon transferlerinde ise amaç çalışan kas grubunun yönünü değiştirerek kas dengesini sağlamaya çalışmaktır.…”
Section: Ortopedik Cerrahi Tedaviunclassified